Pengaruh Kualitas Produk dan Persepsi Harga terhadap Minat Beli Produk Skincare Scarlett di Kota Singaraja - Nadya Valentine Saragih; Made Putri Ariasih (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to test the influence of product quality and price perception on the interest in buying Scarlett skincare products in Singaraja City. This study uses a quantitative method with multiple linear regression analysis techniques. The sample of this study amounted to 110 respondents, which was determined through saturated sampling techniques. Data was collected using a questionnaire and analyzed using the SPSS application version 25. The results of the study show that: (1) product quality has a positive effect on buying interest; (2) price perception simultaneously has a positive effect on buying interest; and (3) product quality and price perception together have a positive effect on buying interest. The results of this study confirm that product quality and price perception have a significant influence on the purchase interest of Scarlett skincare products. The quality of the product referred to in this study includes aspects such as the content of active ingredients, texture, aroma, safety of use, and the final result after use. Meanwhile, price perception includes the extent to which consumers assess the price offered according to the benefits and quality of the product received. Scarlett products themselves are widely known among the public, especially the younger generation, because they have a strong positioning as a local skincare product at an affordable price but still of high quality. With the increasing public interest in personal care, including the use of skincare, it is important for business actors to understand the factors that influence consumer purchasing decisions. The right marketing strategy, such as maintaining consistent product quality and setting competitive prices, can increase consumer loyalty and expand market share. This research is expected to be a reference for brand owners, other researchers, and marketing practitioners in developing relevant business strategies in the competitive beauty industry.